2023
DOI: 10.1001/jamanetworkopen.2023.47519
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood-Level Socioeconomic Status and Prescription Fill Patterns Among Patients With Heart Failure

Amrita Mukhopadhyay,
Saul Blecker,
Xiyue Li
et al.

Abstract: ImportanceMedication nonadherence is common among patients with heart failure with reduced ejection fraction (HFrEF) and can lead to increased hospitalization and mortality. Patients living in socioeconomically disadvantaged areas may be at greater risk for medication nonadherence due to barriers such as lower access to transportation or pharmacies.ObjectiveTo examine the association between neighborhood-level socioeconomic status (nSES) and medication nonadherence among patients with HFrEF and to assess the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 59 publications
0
0
0
Order By: Relevance
“… 67 They also have been shown to exhibit a higher capacity to quit smoking 68 and a better adherence to prescription medications and adherence to cancer screening. 69 , 70 Nouri et al 71 found that documentation of advanced healthcare planning was significantly inferior in patients with lower nSES compared with individuals living in more affluent areas, even after adjusting for amount of care encounters. While education and language barrier can affect patients understanding of treatment instructions and planning, there is a lack of understanding of healthcare providers which factors influence health-seeking behaviors.…”
Section: Discussionmentioning
confidence: 99%
“… 67 They also have been shown to exhibit a higher capacity to quit smoking 68 and a better adherence to prescription medications and adherence to cancer screening. 69 , 70 Nouri et al 71 found that documentation of advanced healthcare planning was significantly inferior in patients with lower nSES compared with individuals living in more affluent areas, even after adjusting for amount of care encounters. While education and language barrier can affect patients understanding of treatment instructions and planning, there is a lack of understanding of healthcare providers which factors influence health-seeking behaviors.…”
Section: Discussionmentioning
confidence: 99%